Dinozor dinosaurs - Leighton, Eric; Zondac, Ralph ([S.l.] : Walt Disney Pictures, 2000)
An orphaned dinosaur raised by lemurs joins an arduous trek to a sancturary after a meteorite shower destroys his family home.
Language : Turkish, English, polski, cesky, magyar, Slovakian, hebrew, Greek.
Subtitle : English, Polski, Ceske, Magyar, Slovakian, Hebrew, Greek.
3-6.
K-3.
Keywords: Movie -- animated films